2003
DOI: 10.1038/sj.bmt.1704084
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of T-, B- and NK-cell reconstitution following conventional or nonmyeloablative conditioning and transplantation with bone marrow or peripheral blood stem cells from human leucocyte antigen identical sibling donors

Abstract: Summary:This retrospective study compares the reconstitution of T, B and NK cells in three groups of patients transplanted for haematological malignancies with grafts from their HLAidentical sibling donors. In all, 15 patients received PBSC after a nonmyeloablative conditioning regimen consisting of fludarabine and 200 cGy TBI, 13 patients received PBSC after myeloablative conditioning and 37 patients received BM after myeloablative conditioning. In the nonmyeloablative group, the NK cells normalised after 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
38
1
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 33 publications
8
38
1
4
Order By: Relevance
“…25 Conversely, we found no significant correlation between IL-15 levels and concurrent T-cell counts. Although both CD8 þ T cells and NK cells are particularly responsive to IL-15, 7,10-12 NK cells recover faster than T cells after HLA-matched RIC-allo-SCT, 12,26,27 which agrees with the negative correlation obtained in this study between IL-15 levels and both NK cell counts, and their downregulated expression of the IL-2/15Rb. Together with declining systemic inflammation, IL-15 consumption by expanding NK cells might explain why systemic levels of the cytokine normalize earlier than those of IL-7.…”
Section: Discussionsupporting
confidence: 81%
“…25 Conversely, we found no significant correlation between IL-15 levels and concurrent T-cell counts. Although both CD8 þ T cells and NK cells are particularly responsive to IL-15, 7,10-12 NK cells recover faster than T cells after HLA-matched RIC-allo-SCT, 12,26,27 which agrees with the negative correlation obtained in this study between IL-15 levels and both NK cell counts, and their downregulated expression of the IL-2/15Rb. Together with declining systemic inflammation, IL-15 consumption by expanding NK cells might explain why systemic levels of the cytokine normalize earlier than those of IL-7.…”
Section: Discussionsupporting
confidence: 81%
“…35,36 CD8 High /CD57 þ T cells arise from peripheral expansion and contribute to the oligoclonal antigen-dependent repertoire, while CD8 Low /CD57 þ are corresponding to NK cells, a cell subset also rapidly reconstituted in our study as usually observed after HSCT. 27 In agreement with previous studies, 20,37,38 we observed rapid NK cell reconstitution, since the median CD3À CD56 þ cell counts were close to the normal values as soon as M þ 1.5.…”
Section: Discussionsupporting
confidence: 80%
“…In contrast to three studies 20,37,38 reporting B-cell reconstitutions (with similar kinetics as our study, that is, low B-cell counts until M þ 7.5 and normal values reached thereafter, 1 year after transplantation) in a context of early high CD4 T-cell counts, we noticed B-cell reconstitution despite long-lasting low CD4 T-cell counts. Low CD4 (helper) T-cell counts may lead to a weaker T-B cooperation and contribute to the lower extensive cGvHD incidence in our study than in these three studies.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Similar results were reported by other authors in smaller series of patients suggesting that survival of host lymphocytes to RIC regimen significantly contributes to immune recovery in these patients in the early period after transplantation. [28][29][30][31] Morecki et al 30 reported no differences in the number of T cells after RIC-SCT in comparison with MAC-SCT; however, RIC regimen hardly lowered the normal T cell-dependent mitogenic response in the first 3 months after transplant.…”
Section: Spotlightmentioning
confidence: 99%